2022
DOI: 10.3892/mmr.2022.12846
|View full text |Cite
|
Sign up to set email alerts
|

COL1A1 expression induced by overexpression of both a 15‑amino acid peptide from the fibrinogen domain of tenascin‑X and integrin α11 in LX‑2 cells

Abstract: Extracellular matrix tenascin-X (TNX) is the largest member of the tenascin family. Our previous study demonstrated that TNX was involved in hepatic dysfunction, including fibrosis, in mice that were administered a high-fat and high-cholesterol diet with high levels of phosphorus and calcium. The present study investigated whether overexpression of both the fibrinogen domain of TNX (TNX-FG) and integrin α11, one of the TNX cell surface receptors, induces in vitro fibrosis in LX-2 human hepatic stellate cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(65 reference statements)
0
1
1
Order By: Relevance
“…Initially, we speculated that TGF-β and TNX-FBG with integrin α11β1 are involved in the induction of COL1A1 expression since interaction of the TNX-FBG domain and TGF-β was reported previously ( Alcaraz et al, 2014 ) and TGF-β is a well-known central mediator of fibrosis ( Dewidar et al, 2019 ). However, contrary to our initial expectation, we found that the Yes-associated protein 1 (YAP1) signaling pathway through integrin α11β1 plays a major role in the induction of COL1A1 expression by expression of the TNX-FBG domain in human hepatic stellate LX-2 cells and that the minimum 15-amino acid (aa) sequence derived from the TNX-FBG domain is required for the induction of COL1A1 expression in the LX-2 cells ( Matsumoto et al, 2022 ). Since integrin α11β1 is known to be a receptor for type I collagen (COL1) and type II collagen ( Zhang et al, 2003 ), it is yet to be determined whether interaction of the TNX-FBG domain with integrin α11β1 is direct or indirect for the induction of COL1A1 expression.…”
Section: Involvement Of Tnx In Fibrosis and Wound Healingcontrasting
confidence: 87%
See 1 more Smart Citation
“…Initially, we speculated that TGF-β and TNX-FBG with integrin α11β1 are involved in the induction of COL1A1 expression since interaction of the TNX-FBG domain and TGF-β was reported previously ( Alcaraz et al, 2014 ) and TGF-β is a well-known central mediator of fibrosis ( Dewidar et al, 2019 ). However, contrary to our initial expectation, we found that the Yes-associated protein 1 (YAP1) signaling pathway through integrin α11β1 plays a major role in the induction of COL1A1 expression by expression of the TNX-FBG domain in human hepatic stellate LX-2 cells and that the minimum 15-amino acid (aa) sequence derived from the TNX-FBG domain is required for the induction of COL1A1 expression in the LX-2 cells ( Matsumoto et al, 2022 ). Since integrin α11β1 is known to be a receptor for type I collagen (COL1) and type II collagen ( Zhang et al, 2003 ), it is yet to be determined whether interaction of the TNX-FBG domain with integrin α11β1 is direct or indirect for the induction of COL1A1 expression.…”
Section: Involvement Of Tnx In Fibrosis and Wound Healingcontrasting
confidence: 87%
“…Finally, we showed that COL1A1 expression was induced by expression of both the 15-aa peptide in the TNX-FBG domain and integrin α11 in hepatic stellate LX-2 cells in vitro ( Matsumoto et al, 2022 ). Further experiments are needed to determine whether expression of the 15-aa peptide from the TNX-FBG domain in liver can induce COL1A1 expression leading to hepatic fibrosis in vivo .…”
Section: Discussionmentioning
confidence: 99%